2020
DOI: 10.14814/phy2.14403
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive short‐term associative conditioning in the pancreatic β‐cell

Abstract: This study associates cholinergic stimulation of the pancreatic β‐cell electrical activity with a short‐term memory phenomenon. Glucose pulses applied to a basal glucose concentration induce depolarizing waves which are used to estimate the evolution of the β‐cell glucose sensitivity. Exposure to carbamoylcholine (carbachol) increases the size of the glucose‐induced depolarizing waves. This change appears after carbachol withdrawal and implies a temporal potentiation of sensitivity (TPS) lasting up to one hour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 65 publications
(85 reference statements)
2
7
0
Order By: Relevance
“…At this rate, the oscillatory behavior would reach a sustained active state (i.e., an active time of 100 %) at approx. 25 mM glucose or somewhat higher, given that the dose-response curve is probably flatter at higher concentrations (124). This is in good agreement with previous insulin secretion data, as well as [Ca 2+ ]IC imaging and electrophysiological studies (9,20,41,57,74,97).…”
Section: Fast [Ca 2+ ] Ic Oscillationssupporting
confidence: 91%
“…At this rate, the oscillatory behavior would reach a sustained active state (i.e., an active time of 100 %) at approx. 25 mM glucose or somewhat higher, given that the dose-response curve is probably flatter at higher concentrations (124). This is in good agreement with previous insulin secretion data, as well as [Ca 2+ ]IC imaging and electrophysiological studies (9,20,41,57,74,97).…”
Section: Fast [Ca 2+ ] Ic Oscillationssupporting
confidence: 91%
“…Assessing Ca 2+ release from intracellular Ca 2+ channels requires high temporal resolution recording. To date, single-cell recording of electrophysiological parameters during glucose-dependent depolarization has been accepted as the gold standard approach to assess the function of a beta cells in islets at a millisecond time scale [15,54]. Until recently, measurements of [Ca 2+ ] c oscillations were typically orders of magnitude slower than this required temporal resolution [44].…”
Section: Introductionmentioning
confidence: 99%
“…Human pancreatic β cells have also demonstrated to exhibit associative conditioning behaviors. In short, temporal potentiation of sensitivity to glucose was achieved by replacing glucose concentrations with other secretagogues in combination with carbachol, giving rise to a newly formed behavior that could be explained by a short-term associative conditioning process ( Sanchez-Andres et al, 2020 ). Electrophysiological studies with individual Purkinje cells have showed that these organisms can remember the interval between the onset of an artificial conditioned stimulus and the onset of an artificial unconditioned stimulus ( Gallistel, 2017 ).…”
Section: Discussionmentioning
confidence: 99%